How Foucault Got Rid of (Bossy) Marxism. Issue 3 (2nd October 2022) - Hull, Gordon
ABSTRACT: Foucault distanced himself from Marxism even though he worked in an environment—left French theory of the 1960s and 1970s—where Marxism was the dominant frame of reference. By viewing Foucault in the context of French Marxist theoretical debates of his day, we can connect his criticisms of Marxism to his discussions of the status of intellectuals. Foucault viewed standard Marxist approaches to the role of intellectuals as a problem of power and knowledge applicable to the Communist party. Marxist party intellectuals, in his view, had developed rigid and universal theories and had used them to prescribe action, which prevented work on the sorts of problems that he uncovered—even though these problems were central to the development of capitalism.